Implementasi Pendidikan Karakter dalam Meningkatkan Kesadaran Pemuda terhadap Lingkungan - Ariyanto Nggilu (Geosfera: Jurnal Penelitian Geografi, 2025)
This study aims to describe the implementation of character education in increasing environmental awareness among youth in Karya Baru Village, Asparaga District, Gorontalo Regency. The research problem stems from the low participation of youth in environmental conservation activities, such as waste management and environmental cleanliness. This study uses a qualitative approach with descriptive methods. Data collection techniques were carried out through observation, interviews, and documentation. The research subjects were village youth, community leaders, and village officials. The results show that the implementation of character education was carried out through youth development activities, mutual cooperation, environmental socialization, and role models from community leaders. The character values developed include responsibility, environmental care, discipline, and mutual cooperation. This implementation has an impact on increasing youth awareness in maintaining cleanliness, reducing littering, and being active in reforestation activities. In conclusion, character education based on national values and social participation is effective in increasing environmental awareness among youth in Karya Baru Village